2012
DOI: 10.1120/jacmp.v13i1.3700
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the feasibility of a simple method for verifying the motion of a binary multileaf collimator synchronized with the rotation of the gantry for helical tomotherapy

Abstract: In this paper, we suggest a new method for verifying the motion of a binary multileaf collimator (MLC) in helical tomotherapy. For this we used a combination of a cylindrical scintillator and a general‐purpose camcorder. The camcorder records the light from the scintillator following photon irradiation, which we use to track the motion of the binary MLC. The purpose of this study is to demonstrate the feasibility of this method as a binary MLC quality assurance (QA) tool. First, the verification was performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…Our results showed a LOT error of − 3.9 ± 7.8% in the reconstructed sinogram compared with the TPS. This outcome is consistent with the − 3.4 ± 8.0% accuracy reported in a previous study by Hashimoto et al [ 19 ]. In a previous study, we demonstrated the feasibility of measuring binary MLC movements using a PS and a general-purpose camcorder.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results showed a LOT error of − 3.9 ± 7.8% in the reconstructed sinogram compared with the TPS. This outcome is consistent with the − 3.4 ± 8.0% accuracy reported in a previous study by Hashimoto et al [ 19 ]. In a previous study, we demonstrated the feasibility of measuring binary MLC movements using a PS and a general-purpose camcorder.…”
Section: Discussionsupporting
confidence: 93%
“…Investigation of the characteristics of the scintillation light detected by our system is necessary to measure MLC opening. Based on the procedure of Hashimoto et al [ 19 ], we investigated the relationship between the scintillation light and LOT. The irradiation field was 10 cm (25–40th leaves opened), and the LOT varied from 29.41 to 294.12 ms for a gantry angle of 0°.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods for the verification of MLC LOTs have been investigated by many authors, some of whom used independent devices, 6 whereas others used the MVCT detector to allow for in vivo dose calculation based on dose reconstruction in the presence of the patient. [7][8][9][10][11][12] We present a QA procedure that involves applying a simple method to measure LOTs with no attenuation between the MLC and the MVCT detector.…”
Section: Introductionmentioning
confidence: 99%
“…This system also allows one to acquire the delivery sinogram during the actual treatment. The sinogram has often been used in the treatment verification [ 12 , 13 ], and one can come up with the visualization of treatment area from the sinogram. For conventional linear accelerators, in fact, CT reconstruction with portal images during rotational treatment such as a volumetric modulated arc therapy (VMAT) has been successfully performed [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%